Disentangling the antecedents of ambidexterity: Exploration and exploitation - Koryak, Oksana; Lockett, Andy; Hayton, James; Nicolaou, Nicos; Mole, Kevin (Elsevier, 2018)
We view ambidexterity as a paradox whereby its components, exploration and exploitation, generate persistent and conflicting demands on an organization. Drawing on the attention based view of the firm (ABV), we examine three antecedents of organizational ambidexterity that reflect ABV’s three principles − the principle of focus of attention; the principle of situated attention; and the principle of structural distribution of attention. Specifically, we examine the influence of top management team (TMT) composition, whether or not the firm has a clear written vision, and the extent to which organizational attention is focused on investments in R&D, and continuous improvement. We empirically validate our model on a sample of 422 small and medium-sized enterprises in the UK and find that ambidexterity is supported by a blend of integration and differentiation approaches.
Keywords: Ambidexterity; TMT; SME; Attention based view